Analisis Pengaruh Pengeluaran Pemerintah Sektor Pendidikan dan Sektor Pariwisata Terhadap Kesejahteraan Masyarakat di Kabupaten Samosir - Damanik, Darwin (Jurnal KAFEBIS, 2024)
Government spending is part of fiscal policy, which is a government action to regulate the course of the economy by determining the amount of government revenue and expenditure. This study aims to determine the effect of government spending in the education sector and tourism sector on community welfare in Samosir Regency for the 2010-2022 period. The method used in this research is quantitative method. The data used is secondary data sourced from the Directorate General of Fiscal Balance (DJPK) and other agencies. And the research model used in this study is a multiple linear regression model (multiple regression) with ordinary least square techniques using the SPSS program. The results of the study concluded that: 1). The Education Sector Government Expenditure Variable has a positive and insignificant effect on Community Welfare in Samosir Regency; 2). The Tourism Sector Government Expenditure Variable has a positive and insignificant effect on Community Welfare in Samosir Regency; 3). Government Expenditure in the Education Sector and Tourism Sector have a joint effect on Community Welfare in Samosir Regency; 4). Adjusted R2 of 0.289 that Government Spending in the Education Sector and the Tourism Sector can explain that the Community Welfare variable in Samosir Regency is 0.289 (28.90%) while the rest is 71.10%.